Formulation and evaluation of transdermal patches of papaverine hydrochloride (Asian Journal of Pharmaceutics (AJP), 2014)
Transdermal patches of papaverine hydrochloride were prepared by the solvent casting method using ethyl cellulose:PVP, PVA: PVP and Eudragit RL-100: Eudragit RS-100 using different ratios. The physicochemical parameters suchas flexibility, thickness, smoothness, weight variation, moisture content, hardness and tensile strength were evaluated forthe prepared patches. The formulation exhibited flexibility, uniform thickness and weight, smoothness, good drug content(92 to 96%), and little moisture content. The in vitro diffusion studies were carried out using modified Keshery-Chein cellusing cellophane as the diffusion membrane and the formulation followed the Higuchi diffusion mechanism. The formulationcontaining PVA: PVP as polymers showed faster release rate (hydrophilic polymers) compared to Eudragit RL-100: EudragitRS-100 (hydrophobic polymers) or combination of hydrophilic and hydrophobic polymers (ethyl cellulose and PVP). Thestability studies indicated that all the patches maintained good physicochemical properties and drug content after storingthe patches in different storage conditions. Compatibility studies indicated that there was no interaction between the drugand polymers. In vivo studies showed that papaverine hydrochloride helps in decreasing the effect of isoproterenol-induced myocardial necrosis. Hence, the aim of the present study was to prepare the sustained release formulation (Transdermal patches) of the drug using different blend of polymers. The formulated patches containing the hydroplilic polymers showed best release rate of drug.Key words: Eudragit RL-100, eudragit RS-100, in vivo study, papaverine hydrochloride, transdermal patch